Analysis of Social and Economic Factors that Influence Work Employee Spirit of UD Mertasari - Pandi Putra Wardana (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of social and economic factors on employee morale at UD Mertasari, which is a multi-business company in Mataram City. The social factors studied include motivation and education, while economic factors include incentives and workload. The research method used was quantitative with an associative approach, using questionnaires distributed to all 45 UD Mertasari employees. The data were analyzed using multiple linear regression with the help of SPSS version 16. The results showed that motivation, incentives, and workload had a positive and significant effect on employee morale, while education had no significant effect. These results confirm that the increase in work morale is more influenced by motivational and economic aspects than formal education background.